Role of ultra-processed foods in modulating the effect of Mediterranean diet on human and planet health—study protocol of the PROMENADE randomized controlled trial - Dinu, Monica; Angelino, Donato; Del Bo’, Cristian; Serafini, Mauro; Sofi, Francesco; Martini, Daniela (Current controlled trials in cardiovascular medicine, 2024)
Background The Mediterranean diet (MD), globally recognized for its sustainability and health benefits, traditionally emphasizes the consumption of plant-based foods in raw or minimally processed forms. However, shifting lifestyles, even in Mediterranean regions, have led to an increasing consumption of ultra-processed foods (UPF). Epidemiological evidence suggests that UPF consumption may be detrimental to human health, but there is only one clinical trial on this topic which is largely debated in the scientific community. This study aims to investigate the impact of the inclusion of UPF within a Mediterranean-based dietary pattern on cardiometabolic markers, gut microbiota, and other markers of human and planet health. Methods Fifty clinically healthy individuals showing overweight and presenting a low-to-moderate cardiovascular risk profile will be recruited for a 7-month randomized, open, cross-over dietary trial. Eligible participants will be randomly assigned to a 3-month high-UPF MD (intervention group) or a low-UPF MD (control group), with a 1-month wash-out period. Both intervention diets will have identical food group compositions, with the intervention group consuming 5 servings/day of selected UPF items, and the control group consuming raw/minimally processed items from the same food group. Blood, urine, and fecal samples, alongside food/lifestyle diaries, will be collected from each participant before and after the dietary interventions. The primary endpoint will be the change in plasma LDL-cholesterol levels from baseline. Additional markers include blood pressure, anthropometric parameters, chemical parameters, glucose and lipid-related metabolic markers, incretins, inflammatory and oxidative stress markers, fecal microbiota composition, and short-chain fatty acids. Finally, food waste production will be evaluated through specific validated food diaries. The study has been approved by the Ethical Committee of the University of Milan and the Tuscany Regional Ethics Committee of the Azienda Ospedaliera Universitaria (AOU) - Careggi, Florence. Discussion Results from the PROMENADE study will improve knowledge about the impact of UPF consumption on human and planet health and will contribute to the scientific debate on this topic. Trial registration ClinicalTrials.gov NCT06314932. Registered on March 13, 2024.